Harmonic content as the indicator of transformer core saturation - Ismail, Daut, Prof. Dr.; Syafruddin, Hassan; Soib, Taib; Risnidar, Chan; Muhammad Irwanto (Institute of Electrical and Electronics Engineers (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/